COLETÂNEA CADERNOS DE SOCIOEDUCAÇÃO (2018): um estudo descritivo sobre a socioeducação no Estado do Paraná. - Gonçalves, Waleria Tominc (2023)
This research aims to carry out a bibliographical and documentary review of socio education in the State of Paraná, focusing our studies on the collection entitled "Cadernos de Socioeducação". Initially, we present the legal issues relating to the subject and how adolescents become involved in crime. In the second chapter, we contextualize the historical evolution of the socio-educational system in Paraná, emphasizing the profile of the adolescent perpetrator of an infraction in that state based on data from 2018. In the third chapter, we highlight the compilation "Cadernos de Socioeducação", which consists of nine notebooks to support work in the socio educational system. Among the obstacles to conducting this work, we concluded that, despite historical progress, the detention measure still stands out, when it should be the exception. In addition, we need to highlight the limits of the Socio-Educational Centers and Semi-Freedom Houses, given that the work carried out sometimes does not reach the families of these adolescents to the point of changing their reality, and once they have served their time, they return to a home that is often disrupted. This highlights the importance of expanding public policies that guarantee all citizens' access to education, health, leisure, and security.